Prospects of Vegetable Crop Production in Northeast Region - Behera, Tusar Kanti; Dubey, Rakesh K (Indian Horticulture, 2024)
Northeastern region is characterized by diverse climate regimes ranging from subtropical to alpine, high rainfall zones, diverse terrain, slopes, altitude, and land tenure systems. Vegetables are cultivated under homestay and mixed commercial systems with various production systems depending on high, mid, and foothills. The region is the wealthiest reservoir of genetic variability of vegetables such as leafy vegetables, tomato, brinjal, chilli, Indian bean, winged bean, velvet bean, tree tomato, tree bean, cucurbits, dioscorea, colocasia, etc. These crops are an integral part of the dietary system of local communities and are grown abundantly in their Jhum land or kitchen garden as mixed cropping. Legume vegetables such as cowpea, French bean, lima bean, Indian bean, velvet bean, winged bean, and leguminous tuber crop Sohphlang are highly suitable for climate-resilient agriculture. Prospects and thrusts in vegetable research for development are highlighted in the paper. The horticulture sector in Northeastern region is moving in the right direction and slowly but steadily moving towards ushering in a new era of golden revolution.